„Bezpieczeństwo to Stany Zjednoczone, gospodarka to interes narodowy” – Korea Południowa wobec rywalizacji amerykańsko-chińskiej - Beczkowska, Joanna (Forms of Power in Contemporary World – Case Studies, 2023)
The US-Chinese rivalry has been a strategic challenge for South Korea for years. Seoul, however, is used to balancing between powers and avoiding the firm support of one side - the most important ally or the largest economic partner. The Korean hedging strategy was based on the paradigm developed over the years: "Security is the United States, the economy is China." Based on "strategic ambiguity" and "balanced diplomacy", this concept separated the spheres of cooperation with the superpowers. However, the intensifying rivalry between the superpowers and the global situation related to the COVID-19 pandemic or Russian aggression against Ukraine changed this paradigm to "security is the United States, the economy is the national interest." The new approach does not mean a departure from hedging against superpowers but points to the need to re-evaluate relations with China. In its strategy, South Korea also seeks greater autonomy from the superpowers in the realm of economic security.